Metacognition Assessment Scale for the Elderly: Validity and Internal Consistency - França, Alex Bacadini (2017)
The aim of this study was to investigate the validity and accuracy of an instrument which assess metacognition in the elderly called Metacognitive Senior Scale (EMETA-S). A sample of 194 elderly of both sexes participated. They answered the EMETA-S, consisting of 74 items. Factor analysis with varimax rotation was performed and revealed the presence of twofactors accounted for 27.18% of the variance of the scale. After deleting items, the EMETA-S was composed of 27 items with internal consistency of 0.85. No signifi cant diff erences were found between the average performance according to the variables of sex, age and education of the participants. The analysis of the validity and accuracy indicated adequacy of the items and good internal consistency of the scale.